Sulfonamides identified as plant immune-priming compounds in high-throughput chemical screening increase disease resistance in Arabidopsis thaliana - Noutoshi, Yoshiteru; Ikeda, Mika; Saito, Tamio; Osada, Hiroyuki; Shirasu, Ken (Frontiers in Plant Science, 2012)
Plant activators are agrochemicals that protect crops from diseases by activating the plant immune system. To isolate lead compounds for use as practical plant activators, we screened 2 different chemical libraries composed of various bioactive substances by using an established screening procedure that can selectively identify immune-priming compounds. We identified and characterized a group of sulfonamide compounds—sulfameter, sulfamethoxypyridazine, sulfabenzamide, and sulfachloropyridazine—among the various isolated candidate molecules. These sulfonamide compounds enhanced the avirulent Pseudomonas-induced cell death of Arabidopsis suspension cell cultures and increased disease resistance in Arabidopsis plants against both avirulent and virulent strains of the bacterium. These compounds did not prevent the growth of pathogenic bacteria in minimal liquid media at 200 µM. They also did not induce the expression of defense-related genes in Arabidopsis seedlings, at least not at 24 and 48 h after treatment, suggesting that they do not act as salicylic acid analogs. In addition, although sulfonamides are known to be folate biosynthesis inhibitors, the application of folate did not restore the potentiation effects of the sulfonamides on pathogen-induced cell death. Our data suggest that sulfonamides potentiate Arabidopsis disease resistance by their novel chemical properties.